Spatial and seasonal variability of dissolved organic matter in the Cariaco Basin. Issue 2 (20th June 2013) - Lorenzoni, Laura; Taylor, Gordon T.; Benitez‐Nelson, Claudia; Hansell, Dennis A.; Montes, Enrique; Masserini, Robert; Fanning, Kent; Varela, Ramón; Astor, Yrene; Guzmán, Laurencia; Muller‐Karger, Frank E.
Abstract: [1] Dissolved organic carbon (DOC), nitrogen (DON), and phosphorus (DOP) were measured monthly at the CARIACO Time Series station (10°30′N, 64°40′W) in the southeastern Caribbean Sea between 2005 and 2012. Marked seasonal variability in DOC concentrations was observed, with lower values (~66 µ M ) in the upper water column (<75 m) during the upwelling season (December–April) due to the injection of cool, DOC‐impoverished Subtropical Underwater from the Caribbean Sea. During the rainy season (May–November) waters were stratified and upper layer DOC concentrations increased to ~71 µ M . Interannual variability in surface (1 m) concentrations of DOC was also observed in response to the variable strength in upwelling and stratification that the Cariaco Basin experienced. DON and DOP showed no such seasonality. At depths >350 m, DOC concentrations were 56 ± 4.7 µ M, roughly 10 µ M higher than those in the Caribbean Sea over the same depth range. DON and DOP showed similar vertical profiles to that of DOC, with higher concentrations (6.8 ± 1.2 µ M N and 0.15 ±0.09 µ M P) in the upper water column and invariant, lower concentrations at depth (4.8 ± 1.6 µ M N and 0.10 ± 0.08 µ M P). Wind‐driven advection of surface DOC out of the Cariaco Basin was estimated to support a net export ~15 Gmol C yr −1 into the Caribbean Sea; this rate is comparable to the flux of settling particulate organic carbon to depths >275 m within the basin. Key Points: We present a 7 year time‐series on DOM in the Cariaco Basin We highlight the importance of microbially‐mediated DOM in anoxic waters The horizontal export of DOC from the Basin varies interannually